The role of public relations communication strategies in building customer trust - Saeed, Asst.Prof.Dr lana Saber Muhammad Saeed; Karim, L.Sazgar Hama Amin Karim (Sulaimani Journal for Humanities, 2025)
In light of rapid economic and social transformations, public relations has become an essential tool for enhancing communication between institutions and their audiences. This research aims to study the role of public relations communication strategies in building customer trust, focusing on communication, dialogue, and persuasion strategies. A descriptive survey methodology was used, relying on data collection from a sample of 320 hotel customers, distributed by gender, age, and educational attainment. Trust and communication strategies were analyzed using statistical means, correlation tests, and regression analysis. The results showed that public relations strategies contribute positively to building trust, with a coefficient of determination (R²) of 0.368, meaning that approximately 36.8% of the variance in trust levels can be explained by these strategies. However, the regression model did not show that any of the three strategies (information, dialogue, and persuasion) had a significant individual impact on trust. The research indicates the need to improve public relations strategies by focusing on the integration of information, dialogue, and persuasion, and combining them with other factors such as service quality and transparency to achieve a greater impact on customer trust.
Keywords: Public relations; communication strategies; trust; media; dialogue; persuasion; the role of the customer